Guide to shareholders' rights - Naylor, Guy. (London : Allen & Unwin, 1969)
The purpose of this book is to explain in straightforward language the relationship between the shareholder and his company, the duties owed by promoters and directors and the information which the shareholder or intending shareholder is entitled to expect from prospectuses, accounts and reports.
Includes bibliographical footnotes and index.
ne 11/07/2018
Loans
Keywords: Stockholders